2016
DOI: 10.1002/anie.201609520
|View full text |Cite
|
Sign up to set email alerts
|

A Bis(silylenyl)pyridine Zero‐Valent Germanium Complex and Its Remarkable Reactivity

Abstract: The synthesis, reactivity, and electronic structure of the unique germylone iron carbonyl complex [SiNSi]Ge →Fe(CO) is reported. The compound was obtained in 49 % yield from the reaction of the bis(N-heterocyclic silylenyl)pyridine pincer ligand SiNSi (1,6-C NH -[EtNSi(N Bu) CPh] ) with GeCl ⋅(dioxane) to give the corresponding chlorogermyliumylidene chloride precursor [SiNSi]Ge Cl Cl , which was further reduced with K Fe(CO) . Single-crystal X-ray diffraction analysis of [SiNSi]Ge→Fe(CO) revealed that the Ge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 51 publications
(25 reference statements)
2
47
0
1
Order By: Relevance
“…The geometric situation is similar to those observed in the NHC‐Mn II complexes [MnCl 2 (C{N( i Pr)C(Me)} 2 ) 2 ] and [MnCl 2 (IMes) 2 ] (IMes=1,3‐dimesitylimidazol‐2‐ylidene) . However, akin to the situation in Fe II and Ge II complexes stabilized by L1 , the pyridine N atom in [L1]MnCl 2 is reluctant in coordinating to the Mn atom as indicated by the relatively long Mn(1)–N(1) distance of 3.259 Å. This is in contrast to PNP pincer‐type Mn II complexes with much shorter N(py)–Mn distances, which can be rationalized by the stronger σ‐donor strength of Si II versus P III towards Mn.…”
Section: Methodssupporting
confidence: 60%
“…The geometric situation is similar to those observed in the NHC‐Mn II complexes [MnCl 2 (C{N( i Pr)C(Me)} 2 ) 2 ] and [MnCl 2 (IMes) 2 ] (IMes=1,3‐dimesitylimidazol‐2‐ylidene) . However, akin to the situation in Fe II and Ge II complexes stabilized by L1 , the pyridine N atom in [L1]MnCl 2 is reluctant in coordinating to the Mn atom as indicated by the relatively long Mn(1)–N(1) distance of 3.259 Å. This is in contrast to PNP pincer‐type Mn II complexes with much shorter N(py)–Mn distances, which can be rationalized by the stronger σ‐donor strength of Si II versus P III towards Mn.…”
Section: Methodssupporting
confidence: 60%
“…Synthesis of germylone complexes 45 and 46. [42] Figure 32. Molecular structureso fgermylone complexes (a) 45 and (b) 46 (botha nions omitted for clarity).…”
Section: Discussionmentioning
confidence: 99%
“…While complexes 40 – 42 were prepared by the simple complexation of germylone 30 , iron complex 45 , which is the iron complex of germylone 44 , was synthesized by the simultaneous reduction and complexation of the precursor of the germylone (Scheme ). That is, the reaction of 43 , which was prepared by the reaction of the corresponding ligand with GeCl 2 ⋅dioxane, with K 2 [Fe(CO) 4 ] resulted in the formation of germylone complex 45 (Scheme ) . It was found that the pyridine moiety of 45 coordinates to one of the silylene moiety, forming its unsymmetrical structure.…”
Section: The Reactivity Of Tetrylonesmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Unfortunately the use of these bulky substituents restricted access to the HBNH array by potential reagents/catalysts. In this Edge Article we introduce a more reactive HBNH adduct and describe our attempts to convert this species into LB·BN·LA complexes (LA = Lewis acid; LB = Lewis base; Scheme 1); in addition we investigate the reactivity of the donor-stabilized azidohydride boronium cation [BH(N 3 )] + .…”
Section: Introductionmentioning
confidence: 99%